ANALISIS KESEJAHTERAAN PEKERJA PENGOLAH MINYAK KELAPA SAWIT PT. WAWASAN KEBUN NUSANTARA SELAMA PANDEMI COVID - Arif, Dorius; Ulfah, Maria; Ramadhan, Iwan (Universitas Tanjungpura, 2023)
During the Covid-19 pandemic at PT Wawasan Kebun Nusantara, palm oil processing workers were still working at the factory as usual. While working, palm oil processing workers are still required to be professional in carrying out work activities. Moreover, the demand for palm oil production continues to increase. With the Covid-19 pandemic, workers are actually obliged to get protection. This is because working during the Covid-19 pandemic is more at risk of contracting the virus because it is in a busy environment and meets many people. This study aims to examine the welfare program of palm oil processorsat PT Wawasan Kebun Nusantara in Sentanggau Jaya Village during the COVID-19 pandemic. Worker welfare is the company's responsibility to workers to ensure cooperation between employers ofworkers, where employee welfare programs have three indicators, namely economic welfare programs, facility welfare programs, and service welfare programs. The role of the company is carried out from preventing, treating and providing health insurance for its workers during the covid-19 pandemic. This must be done by companies both preventively and reactively to protect all palm oil processing workersduring the COVID-19 pandemic.